Comparison of Radiation Response between 2D and 3D Cell Culture Models of Different Human Cancer Cell Lines - Raitanen, Julia; Barta, Bernadette; Hacker, Marcus; Georg, Dietmar; Balber, Theresa; Mitterhauser, Markus (Cells (Basel, Switzerland), 2023)
Radiation therapy is one of the most effective tools in cancer therapy. However, success varies individually, necessitating improved understanding of radiobiology. Three-dimensional (3D) tumor spheroids are increasingly gaining attention, being a superior in vitro cancer model compared to 2D cell cultures. This in vitro study aimed at comparing radiation responses in 2D and 3D cell culture models of different human cancer cell lines (PC-3, LNCaP and T-47D) irradiated with varying doses (1, 2, 4, 6, 8 or 20 Gy) of X-ray beams. Radiation response was analyzed by growth analysis, various cell viability assays (e.g., clonogenic assay, resazurin assay) and amount of DNA damage (γH2AX Western Blot). Results showed decreasing cell proliferation with the increase of radiation doses for all cell lines in monolayers and spheroids of LNCaP and T-47D. However, significantly lower radiosensitivity was detected in spheroids, most pronounced in PC-3, evincing radiation resistance of PC-3 spheroids up to 8 Gy and significant growth inhibition only by a dose escalation of 20 Gy. Cell line comparison showed highest radiosensitivity in LNCaP, followed by T-47D and PC-3 in 2D, whereas, in 3D, T-47D showed highest sensitivity. The results substantiate the significant differences in radiobiological response to X-rays between 2D and 3D cell culture models.